Effects of an acute bout of exercise on salivary lactoferrin responses among sedentary smokers and non-smokers men - Muhamad, Ayu Suzailiana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2019)
The purpose of this study is to determine the effects of an acute bout of exercise on sa)jvary lactoferrin responses among smokers and non· smokers. Eighteen sedentary men were recruited; nine smokers (age = 22.4 ± 1.4 years; BM1 = 22. I ± 1.1 kglm2) arul nine non-smokers (age = 22. 1 ± 0.7 years old; BM1 = 22.5 ± 1.9 kg!m2). In this study, participants cycled at an intensity of 60% tnaxjmum heart rate for 60 minutes. Pamcipants were given cool water as much as 3 ml!kg body weight at minutes 20 and 40 during the exercise session. Participants' body weight and saliva samples were collected at pre and post-exercise. Heart rate and rate of perceived exertion (RPE) were recorded at pre, during and post-exercise. Mixed ANOVA was used to measure significant differences between groups and within group. The resuJts showed that sa)jva flow rate, lactoferrin concentration and lactoferrin secretion rate were not significantly di!Terent (p>O.OS) between smokers and non-smokers groups and also between pre and post-exercise withjn each group. Heart rate and RPE showed significant increased (p<0.05) during the exercise session in both groups. As a conclusion, acute bout of exercise docs not affect salivary lactoferrin responses among sedentary smokers and non-smokers men.